POLA KOMUNIKASI IBU PEMAIN AKTIF GAME ROBLOX TERHADAP ANAK UNTUK MENCEGAH DAMPAK NEGATIF GAME ROBLOX - Talitha Nakhwah Syldman; Rahmawati, Dian Hutami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has significantly increased children's use of online games like Roblox. While beneficial for entertainment, creativity, and social interaction, Roblox potentially causes negative impacts, such as gaming addiction, decreased learning concentration, health problems, and changes in social behavior. Consequently, mothers play an important role in supervising and establishing effective communication to prevent these negative effects. This study aims to describe the communication patterns employed by mothers who actively play Roblox with their children to prevent these impacts. This research used a descriptive qualitative approach with a constructivist paradigm. Informants were selected through purposive sampling, comprising mothers and children who actively play Roblox. Data were collected through in-depth interviews, documentation, and literature studies, then analyzed via data reduction, presentation, and conclusion drawing. Applying Rational Dialectics Theory—including reason-giving, two-way dialogue, and negotiation and agreement—as the analytical framework, the findings indicate that mothers implement persuasive, educational, empathetic, and assertive communication patterns. These are manifested through logical explanations regarding excessive gaming risks, two-way discussions about gaming activities, and agreements concerning playing duration and permissible content. Additionally, mothers supervise in-game interactions, provide digital safety education, and encourage a balance between gaming, learning, and social activities. The study concludes that open, dialogical, and agreement-based communication enhances children's awareness of responsible Roblox use and minimizes its negative impacts.